A Multidimensional Approach to Digital Customer Engagement: Empirical Study of Live-Streaming Communication Attributes - Putri Farah Fadhiilah; Popy Rufaidah (Media Ekonomi dan Manajemen, 2025)
This study examines the impact of live-streaming on digital customer engagement by focusing on three key communication attributes: communication immediacy, interactivity, and visualization. The research investigates how these attributes influence cognitive, emotional, and behavioral engagement. A quantitative method was employed, using data collected through an online survey distributed to users who interact with brands via live-streaming platforms. The dataset was analysed using Partial Least Squares Structural Equation Modelling (SEM-PLS). The results indicate that communication immediacy and interactivity significantly affect all three dimensions of digital customer engagement. In contrast, visualization only has a significant impact on emotional engagement, while its influence on cognitive and behavioral engagement is not supported. These findings suggest that not all live-streaming features equally drive customer engagement. The study contributes to the growing literature on digital engagement and provides practical insights into how brands can strengthen real-time interactivity and emotional resonance to foster deeper consumer involvement.